Captain Underpants and the Tyrannical Retaliation of the Turbo Toilet 2000 : Captain Underpants #11 - Pilkey, Dav, 1966- (New York, NY : Scholastic Inc., 2014)
The monstrous Turbo Toilet 2000 is determined to take revenge on George, Harold, and Captain Underpants.
Keywords: Captain Underpants (Fictitious character) -- Juvenile fiction; School principals -- Juvenile fiction; Monsters -- Juvenile fiction; Superheroes -- Juvenile fiction; School principals -- Fiction; Monsters -- Fiction; Superheroes -- Fiction; Humorous fiction; Humorous fiction